Copper-catalysed N-arylation of 5-aminopyrazoles: a simple route to pyrazolo[3, 4-b]indoles. Issue 33 (14th August 2020) - Chatterjee, Arpita; Murmu, Chudamani; Peruncheralathan, S.
Abstract : Two classes of pyrazolo fused N-heterocycles are synthesized from 5-aminopyrazoles using an inexpensive and non-toxic CuCl catalyst. The N -arylation process is very selective and does not require any ligands. Abstract : A copper-catalysed intramolecular N -arylation of 5-aminopyrazoles is demonstrated for the first time. Highly substituted pyrazolo[3, 4- b ]indoles are synthesized. In particular, the indole core is decorated with halogens and alkyl and methoxy groups. Furthermore, a selective N -arylation of unsymmetrical diaryl bromide containing pyrazoles is exemplified, resulting in valuable pyrazolo[1, 5- a ]benzimidazoles.